From narratives to numbers: Spatial downscaling and quantification of future water, food & energy security requirements in the Indus basin. (October 2021) - Smolenaars, Wouter J.; Lutz, Arthur F.; Biemans, Hester; Dhaubanjar, Sanita; Immerzeel, Walter W.; Ludwig, Fulco
Highlights: We present three spatially explicit scenarios for future water, food and energy security requirements in the Indus basin. Water and energy requirements in the basin are projected to potentially triple, while food requirements may double at most. The increase in resource requirements converges around the basin's largest cities due to urbanisation and population change. Policy makers and integrated modelling studies must account for the spatial heterogeneity in future resource security challenges when designing adaptation strategies. Abstract: Integrated adaptation strategies are needed to achieve the highly interlinked Sustainable Development Goals (SDGs) for water, food- and energy security in the Indus basin. However, detailed quantitative scenarios for the plausible dimensions of future resource security requirements under socio-economic development are lacking. Here we define three quantitative and spatially downscaled scenarios for future water, food and energy requirements in the Indus basin and we assess the implications of socio-economic development for the integrated resource security challenge. High-resolution gridded scenarios for resource security requirements are developed by combining three regionalised and spatialised Shared Socioeconomic Pathways (SSPs) with quantitative regional water, food and energy security thresholds. The results demonstrate that by 2080 basin level water- and energy security requirements are likely to at least double and potentially triple compared to the current situation. Food requirements could increase only marginally and double at most. Migration and urbanisation additionally drive the growing requirements to spatially converge around the largest cities of the basin. This demonstrates that socio-economic development increases the complexity of the water-food-energy security challenge by increasing its magnitude and spatial concentration. Future research and policymaking should anticipate for this heterogeneous growth of resource security challenges when developing adaptation strategies.